Phytochemical screenings, thrombolytic activity and antimicrobial properties of the bark extracts of Averrhoa bilimbi - Kamrul Islam Siddique, Mir Muhammad Nasir Uddin, Md. Siddiqul Islam, Salma Parvin and Mohammad Shahriar (Journal of Applied Pharmaceutical Science, 2013)
In this present study, the bark extracts of Averrhoa bilimbi were subjected to the thrombolytic activities were assessed by using human erythrocyte and the results were compared with standard streptokinase (SK). On the other hand, bark extracts of A. bilimbi revealed moderate antibacterial activity against some microorganisms used in the screening. Preliminary phytochemical investigation suggested the presence of flavonoids, saponins and alkaloids.
Keywords: Thrombolytic activity, Averrhoa bilimbi,&lt